Combining probabilistic neural networks and decision trees for maximally accurate and efficient accident prediction - Tambouratzis, Tatiana; Souliou, Dora; Chalikias, Miltiadis; Gregoriades, Andreas (My University, 2010)
The extent to which accident severity can be predicted from accident-related data collected at a variety of locations is investigated. The 2005 accident dataset brought together by the Republic of Cyprus Police is employed; this dataset comprises 1407 records of 43 continuous and categorical input parameters and a single categorical output parameter representing accident severity. No transformation of the database has been opted for, either by extracting the parameters that are significant for the prediction task or by modifying the records in any way (e.g. via record selection or transformation). Aiming at maximally accurate and efficient prediction, a combination of probabilistic neural networks (PNN's) and decision trees (DT's) is implemented: the simple training and direct operation of the PNN is complemented by the hierarchical, exhaustive and recursive construction of the DT. By training pairs of PNN's on data from the partitions derived from the minimal necessary number of top DT nodes, both efficiency and accident prediction accuracy are maximized. © 2010 IEEE.
Keywords: Accident prediction; Accident severity; Data sets; Input parameter; Output parameters; Probabilistic neural networks